Effect Of Rotor Blade Wing Tip On Wind Turbine Performance Using Naca 0018 Blade - Ibnu Mas'ud; Rachmad Firdaus (Procedia of Engineering and Life Science, 2021)
Indonesia currently has a growing need for energy, this will experience an energy crisis, dependence on fossil fuels will at least have a serious threat, therefore there must be alternative energy as a substitute and reserve such as wind energy, water energy, solar energy, and other. This study aims to develop a wind power plant as an alternative source to produce electrical energy, namely a wind turbine. This tool is used to meet energy needs and also as an alternative energy so that fossil fuels will not run out. Because Indonesia is an archipelagic country and is located on the equator, Indonesia is a country that has abundant resources, one of which is wind. Wind turbine is a tool that functions to convert wind power into mechanical power in the form of a shaft rotation, this shaft rotation is then used for power generation or for water pumps. Therefore I tried to develop my ideas to utilize abundant natural resources to be used as a source of electrical energy by means of a wind turbine using a Naca 0018 blade. This study aims to determine the effect of the number of blades, the effect of profiles, the effect of the wing tip of the rotor blades. , naca 0018, and the resulting energy efficiency. This study uses the type of experimental research.